Geometric Control Theory for Linear Systems: a Tutorial - Marro, G.; Morbidi, F.; Ntogramatzidis, Lorenzo; Prattichizzo, D. (MTA SZTAKI, 2010)
This paper reviews in a condensed form the main tools and results of the geometric approach developed in thelast forty years. Because of the vastness of the subject, this tutorial does not pretend to be exhaustive, and more emphasis will be given to selected topics and to the related computational tools. The authors hope their effort to provide a unified view of geometric control theory may be profitable to awake renewed interest in this research field.